SCIL-STROKE (Subcutaneous Interleukin-1 Receptor Antagonist in Ischemic Stroke): A Randomized Controlled Phase 2 Trial. Issue 5 (May 2018) - Smith, Craig J.; Hulme, Sharon; Vail, Andy; Heal, Calvin; Parry-Jones, Adrian R.; Scarth, Sylvia; Hopkins, Karen; Hoadley, Margaret; Allan, Stuart M.; Rothwell, Nancy J.; Hopkins, Stephen J.; Tyrrell, Pippa J.
Abstract : Background and Purpose—: The proinflammatory cytokine IL-1 (interleukin-1) has a deleterious role in cerebral ischemia, which is attenuated by IL-1 receptor antagonist (IL-1Ra). IL-1 induces peripheral inflammatory mediators, such as interleukin-6, which are associated with worse prognosis after ischemic stroke. We investigated whether subcutaneous IL-1Ra reduces the peripheral inflammatory response in acute ischemic stroke. Methods—: SCIL-STROKE (Subcutaneous Interleukin-1 Receptor Antagonist in Ischemic Stroke) was a single-center, double-blind, randomized, placebo-controlled phase 2 trial of subcutaneous IL-1Ra (100 mg administered twice daily for 3 days) in patients presenting within 5 hours of ischemic stroke onset. Randomization was stratified for baseline National Institutes of Health Stroke Scale score and thrombolysis. Measurement of plasma interleukin-6 and other peripheral inflammatory markers was undertaken at 5 time points. The primary outcome was difference in concentration of log(interleukin-6) as area under the curve to day 3. Secondary outcomes included exploratory effect of IL-1Ra on 3-month outcome with the modified Rankin Scale. Results—: We recruited 80 patients (mean age, 72 years; median National Institutes of Health Stroke Scale, 12) of whom 73% received intravenous thrombolysis with alteplase. IL-1Ra significantly reduced plasma interleukin-6 ( P <0.001) and plasma C-reactive protein ( P <0.001). IL-1Ra was well tolerated with no safety concerns. Allocation to IL-1Ra was not associated with a favorable outcome on modified Rankin Scale: odds ratio (95% confidence interval)=0.67 (0.29–1.52), P =0.34. Exploratory mediation analysis suggested that IL-1Ra improved clinical outcome by reducing inflammation, but there was a statistically significant, alternative mechanism countering this benefit. Conclusions—: IL-1Ra reduced plasma inflammatory markers which are known to be associated with worse clinical outcome in ischemic stroke. Subcutaneous IL-1Ra is safe and well tolerated. Further experimental studies are required to investigate efficacy and possible interactions of IL-1Ra with thrombolysis. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: ISRCTN74236229 Abstract : Supplemental Digital Content is available in the text.